Genetics in Atopic Dermatitis: Historical Perspective and Future Prospects - Sara J. Brown; Martina S. Elias; Maria Bradley (Medical Journals Sweden, 2020)
Atopic dermatitis (AD) is a common, complex trait, arising from the interplay of multiple genetic and environmental factors. This review provides an overview of developments in the field of AD genetics. AD shows high heritability; strategies to investigate genetic risk include linkage, candidate gene studies, genome-wide association and animal modelling. Loss-of-function mutations in FLG, encoding the skin barrier protein filaggrin, remain the strongest genetic risk factor identified for AD, but variants influencing skin and systemic immune function are also important. AD is at the forefront of genetic research, from large-scale population studies to in vitro models and detailed molecular analyses. An understanding of genetic risk factors has considerably improved knowledge of mechanisms leading to atopic skin inflammation. Together this work has identified avenues for therapeutic intervention, but further research is needed to fully realise the opportunities of personalised medicine for this complex disease, to optimise patient benefit.